PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN SEPAK BOLA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the application of the Problem-Based Learning model in soccer learning and its impact on learning outcomes, motivation, and critical thinking skills of students at SMA Negeri 1 Medan. This study used a qualitative, descriptive approach. The research subjects were determined purposively, consisting of physical education teachers and students. Data collection techniques were conducted through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the application of the Problem-Based Learning model can increase student engagement, understanding, and motivation through interactive, problem-based learning. Despite obstacles such as time constraints, uneven participation, and limited resources, this model remains effective in improving the quality of soccer learning.